Predictors for timely initiation of breastfeeding after birth in the hospitals of Nepal- a prospective observational study - Rejina Gurung; Avinash K. Sunny; Prajwal Paudel; Pratiksha Bhattarai; Omkar Basnet; Srijana Sharma; Durgalaxmi Shrestha; Seema Sharma; Honey Malla; Dela Singh; Sangeeta Mishra; Ashish KC (BMC, 2021)
Abstract Background Timely initiation of breastfeeding can reduce neonatal morbidities and mortality. We aimed to study predictors for timely initiation of breastfeeding (within 1 h of birth) among neonates born in hospitals of Nepal. Method A prospective observational study was conducted in four public hospitals between July and October 2018. All women admitted in the hospital for childbirth and who consented were included in the study. An independent researchers observed whether the neonates were placed in skin-to-skin contact, delay cord clamping and timely initiation of breastfeeding. Sociodemographic variables, obstetric and neonate information were extracted from the maternity register. We analysed predictors for timely initiation of breastfeeding with Pearson chi-square test and multivariate logistic regression. Results Among the 6488 woman-infant pair observed, breastfeeding was timely initiated in 49.5% neonates. The timely initiation of breastfeeding was found to be higher among neonates who were placed skin-to-skin contact (34.9% vs 19.9%, p - value < 0.001). The timely initiation of breastfeeding was higher if the cord clamping was delayed than early cord clamped neonates (44.5% vs 35.3%, p - value < 0.001). In multivariate analysis, a mother with no obstetric complication during admission had 57% higher odds of timely initiation of breastfeeding (aOR 1.57; 95% CI 1.33, 1.86). Multiparity was associated with less timely initiation of breastfeeding (aOR 1.56; 95% CI 1.35, 1.82). Similarly, there was more common practice of timely initiation of breastfeeding among low birthweight neonates (aOR 1.46; 95% CI 1.21, 1.76). Neonates who were placed skin-to-skin contact with mother had more than two-fold higher odds of timely breastfeeding (aOR 2.52; 95% CI 2.19, 2.89). Likewise, neonates who had their cord intact for 3 min had 37% higher odds of timely breastfeeding (aOR 1.37; 95% CI 1.21, 1.55). Conclusions The rate of timely initiation of breastfeeding practice is low in the health facilities of Nepal. Multiparity, no obstetric complication at admission, neonates placed in skin-to-skin contact and delay cord clamping were strong predictors for timely initiation of breastfeeding. Quality improvement intervention can improve skin-to-skin contact, delayed cord clamping and timely initiation of breastfeeding.